CHANGES IN UKRAINIAN SPELLING AS A FACTOR OF NATIONAL SECURITY (Coordinates of Public Administration, 2026)
The article, through the prism of current issues in Ukraine and the historical prerequisites of this situation, examines the problem of the contamination of the Ukrainian national language with copied Russian-language forms and models, which is not only an objective result of historical bilingualism, but also a result of the subjective negative attitude of the empire and its leaders towards Ukraine and Ukrainians, which led to cases of linguocide and ethnocide caused by the corresponding imperial policy. The defining connection between the concepts of «Ukrainian national identity», «Ukrainian-Russian bilingualism», «imperial essence of the Russian language», «structural stability of the Ukrainian language» and, ultimately, «departure from the Russian language and culture» in the context of the resistance of the Ukrainian people to imperial terrorist aggression is traced. It is noted that this aggression is aimed, among other things, at leveling (eliminating, destroying) the Ukrainian language as perhaps the most important factor threatening the existence of the Russian / Soviet empire as such. It is proven that the structure of the Ukrainian language is significantly violated by its business/scientific style, in which state documents (laws and by-laws) are written, because it is most littered with Russian-language calques. Specific examples of possible changes in the spelling of the Ukrainian language are given.It is concluded that the new edition of the spelling, even codifying specific Ukrainian-language forms and models in place of calques, will not fundamentally change the situation, because only language specialists will react to it. In addition, in order for society to realize these changes, a large online dictionary will be needed, access to the resources of which will be convenient and easy for any user. But that's not all: citizens need to be aware that the renewed national (state) language is also a weapon against the imperialist enemy.